1984
DOI: 10.1111/j.1439-0434.1984.tb00727.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Strain of Cucumber Mosaic Virus Causing Mosaic Disease of Muskmelon

Abstract: The virus causing mosaic of muskmelon in the Punjab is transmitted through seed, sap and aphids but not through beetle, whitefly, fungi or contact. It systemically infected Nicotiana tabacum (var. “White Burley” and CTRI‐Special), N. glutinosa, N. rustica and Capsicum annuum besides various cucurbit hosts when inoculated mechanically. The virus gave positive reaction with the antiserum of cucumber mosaic virus and the particles are spherical in shape. The virus has been identified as a distinct strain of cucum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Sharma and Chohan (1974) reported that the rate of CMV seed infection in pumpkin was 0.7%. It was reported from India that CMV can be transmitted through melons seeds (Sharma et al, 1984). Tóbiás et al (2008) reported that from 225 seedborne virus infected plants of hulless oilseed pumpkin (Cucurbita pepo), a total of 166 had ZYMV (Zucchini yellow mosaic virus) and 59 had mixed infection of ZYMV and CMV as identified by ELISA test indicator plants and RT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Sharma and Chohan (1974) reported that the rate of CMV seed infection in pumpkin was 0.7%. It was reported from India that CMV can be transmitted through melons seeds (Sharma et al, 1984). Tóbiás et al (2008) reported that from 225 seedborne virus infected plants of hulless oilseed pumpkin (Cucurbita pepo), a total of 166 had ZYMV (Zucchini yellow mosaic virus) and 59 had mixed infection of ZYMV and CMV as identified by ELISA test indicator plants and RT-PCR.…”
Section: Discussionmentioning
confidence: 99%